A review of integrated river basin management for Sarawak River - Kuok, King Kuok (Science Publications, 2011)
Problem statement: Sarawak River was a life-sustaining water source for the residents in Kuching City and surrounding areas. Raw water is treated at Batu Kitang Water Treatment Plant (BKWTP) that supplies more than 98% of the total water production in Kuching City. The raw water supply to BKWTP is not adequate to meet the ever increasing water demand. In order to overcome this problem, four projects had been implemented along Sarawak River for managing and securing water supply to BKWTP. Approach: These four projects are construction of 1.5m height storage weir across Sungai Sarawak Kiri river channel, Kuching Barrage and Shiplock, Bengoh Dam and Kuching Centralized Wastewater Management System (KCWMS). In 2005, 1.5 m height submersible weir was constructed across Sungai Sarawak Kiri channel for increasing the safe yield that can last until year 2010. Kuching Barrage and Shiplock were commissioned in 2000 as barrier to avoid the saline intrusion reaching upper catchment. 24 telemetry stations were installed along Sarawak River for monitoring and regulating the water level. This will preserve high quality water storage at upper catchment of Sarawak River. In year 2010, Bengoh Dam was constructed to ensure adequate raw water will be supplied to BKWTP for meeting the increasing water demand from 2010-2030. This reservoir will store 144 million m3 of fresh water covering reservoir area of 8.77km2 . Beyond 2030, the water supply shall not depend solely on fresh water. Results: Black and grey water in Sarawak Catchment was treated through Kuching Centralized Wastewater Management System (KCWMS) and recycled for daily used. Conclusion: The treated water that comply Standard A water quality, can distribute for domestic, industrial and irrigation used in nearest future. This will reduce the water demand solely on raw water and create a sustainable living in Kuching City. Beyond 2030, a few alternatives are also proposed for conserving and securing water supply for Kuching city.